Seorang Penderita dengan Retrosternal Goiter: [A Patient with Retrosternal Goiter: A Rare Case] - Mawardi Mawardi; Daniel Maranatha (Faculty of Medicine Universitas Airlangga, 2016)
Background: Retrosternal goiter of the thyroid gland is the inclusion of 50% or more into the thoracic cavity. Many terms are used to describe the entry of the thyroid gland into the thoracic cavity include: substernal goiter, intrathoracic goiter, retrosternal goiter and mediastinal goitre. Case: We report the case of a woman with retrosternal goiter initially suspected as a tumor in the mediastinum. Patients present with chest pain and no visible enlargement of the thyroid gland in the neck. On examination thoracic CT scan and found an enlarged thyroid gland in the chest cavity is then performed total thyroidectomy surgery and sternotomy. Conclusion: This case illustrates retrosternal goiters should be differentiated from other mediastinal masses by appropriate work-up, while computed tomography is the most valuable technique and surgical management is mandatory.